THE INFLUENCE OF E-SERVICE QUALITY, PROMOTIONS, HALAL LIFESTYLE, AND ISLAMIC BRANDING ON DECISIONS TO PURCHASE HALAL PRODUCTS IN E-COMMERCE (CASE STUDY ON SHOPEE BAROKAH FEATURE) - Madyaning Sri Utami; Febrian Wahyu Wibowo; Al-Haq Kamal; Rusny Istiqomah Sujono (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to examine the influence of e-service quality, promotions, halal lifestyle, and Islamic branding on purchase decisions of halal products through the Shopee Barokah feature. Using a quantitative approach, data were collected from 100 respondents selected through purposive sampling. The analysis method employed is multiple linear regression. The results reveal that e-service quality and halal lifestyle have a positive and significant effect on purchase decisions. However, promotions and Islamic branding do not significantly influence purchase decisions. These findings suggest that Muslim consumers are more influenced by service quality and lifestyle compatibility with Islamic values than by promotional strategies or religious branding alone. This study provides practical implications for e-commerce platforms in enhancing service quality and aligning their offerings with the values of Muslim consumers.